2000
DOI: 10.1557/proc-636-d9.8.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Assembling Method for Nano-sized Particles Using an Electrified Pattern Drawn by a Focused Ion Beam

Abstract: This paper describes a new technique to fabricate two-dimensional microstructures assembled with nano-sized particles. The nano-sized particles attract a lot of attention because of their unique properties compared to bulk materials. Micro-and nano-structures assembled with nano-sized particles have potential applications in electronic, optical and biochemical fields. The Self-Assembled Monolayer (SAM) film patterning is one of the methods to assemble the nano-sized particles. We have proposed a new method to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As a result, several research groups have begun investigating charge based printing. Krinke et al [34] assembled indium particles from the gas phase onto charged areas created by contact charging using a scanning stainless steel needle and a nickel plate; Mesquida et al [27,35] demonstrated the assembly of silica beads and gold colloids from the liquid phase onto charged areas created by contact charging using a scanning probe and Fudouzi et al [29,36] demonstrated the assembly of SiO 2 and TiO 2 particles from both the liquid and gas phases onto charged areas created by focused ion and electron beams. Our parallel nanoxerographic process [26] provides the ability to fabricate numerous charged samples in a reasonable amount of time.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, several research groups have begun investigating charge based printing. Krinke et al [34] assembled indium particles from the gas phase onto charged areas created by contact charging using a scanning stainless steel needle and a nickel plate; Mesquida et al [27,35] demonstrated the assembly of silica beads and gold colloids from the liquid phase onto charged areas created by contact charging using a scanning probe and Fudouzi et al [29,36] demonstrated the assembly of SiO 2 and TiO 2 particles from both the liquid and gas phases onto charged areas created by focused ion and electron beams. Our parallel nanoxerographic process [26] provides the ability to fabricate numerous charged samples in a reasonable amount of time.…”
Section: Introductionmentioning
confidence: 99%
“…14 Since then, several serial chargepatterning processes have been explored to enable the positioning of nanoparticles. 15,[17][18][19] Serial techniques, however, remain slow-the fastest scanning probe-based system needs 1.5 days to pattern an area of 1 cm 2 . 20 As a new direction, we have developed a parallel charge patterning process 16 enabling nanoxerographic printing.…”
mentioning
confidence: 99%